APPLICATION OF K-MEANS ALGORITHM ON FAVORITE MENU SELECTION AT WARUNG NASI ALAM SUNDA - Neneng Komariah; Yusef Bintang Fajar; Sudin Saepudin; Muhamad Muslih; Lisnawati Fitriyani (Nusa Putra University, 2022)
Warung Nasi Alam Sunda is a stall that does sundanese culinary business that serves several dishes of various vegetables, soto, chicken, fish, and others. In the application of favorite menu, Warung Nasi Alam Sunda determines it randomly, so it does not match the report given. This research aims to assist the restaurant in determining the favorite menu. This research uses data mining techniques with K- Means. Input attributes in this study include price, taste, favorites. In this study, it can be produced that the results of grouping into 3 groups namely c- 1=fried chicken, c-2=fried carp and c-3=soto betawi. After 9 iterations, the 8th and 9th results are the same as c-1=9, c-2=22 and c-3=16. Then get the highest result as follows fried chicken=53, oxtail soup=49 and intestinal satay=42. Judging from the largest to smallest order of the sample 47 variables taken only 3 representatives. So the highest result is fried chicken. That will be the favorite menu at Warung Nasi Alam Sunda. System design using UML, system implementation using PHP and MySQL. The goal that this study wanted to achieve was to be able to cluster your favorite food menus using the K-Means algorithm